Counseling intervention for native mothers of Autism Spectrum Disorder (ASD) children - Chan Wei, Sian (Universiti Malaysia Sarawak (UNIMAS), 2018)
The purpose of this study was aim to explore about the experiences of native mothers with autistic children in Kuching, Sarawak This research focused on exploration about the challenged faced by native mothers with autistic children, their coping strategies, and participation in counseling intervention. The research design of this study is qualitative approach and employed face-to-face interview session with participant. Interview session took time for 30 minutes until 45 minutes and semi-structured interview session was used to collect data. Three native mothers with autistic child involved in the interview session while one native mother with autistic child participated in pilot study. Four major themes and nine sub-themes have been identified based on interview result. Four major themes consist of experiences of native mothers, challenges faced by native mothers, coping strategies, and participation in counseling intervention. Nine sub-themes include children's condition, family's acceptance, lack of autism-related resources and support, low awareness of society, self-commitment, assistance from family and agencies, and mother's experiences and expectation. The result of this research is quite interesting because native mothers with autistic child experienced low level of stress in the process of raising up an autistic child and it is contradict with the result of previous research. However, there is some limitations in this research and future work is needed in order to improve this research by involve various population such as Sarawakian and Sabahan, involvement of fathers of autistic children, and mixed-method approach can be applied in further research in order to get more precise information.